Controlled formation of uniform CeO2 nanoshells in a buffer solution. Issue 7 (8th December 2015) - Zhang, Wei; Yang, Li-Ping; Wu, Zi-Xiao; Piao, Jun-Yu; Cao, An-Min; Wan, Li-Jun
Abstract : Uniform CeO2 nanoshells were successfully prepared by using MOPS buffer solution as a unique growth medium. Abstract : Uniform CeO2 nanoshells were successfully prepared by using buffer solution as a unique growth medium. The application of this methodology to construct a yolk–shell structured Au@CeO2 nanocatalyst shows improved performance for the catalytic CO oxidation.